Mycobacterial mannose-capped lipoarabinomannan: a modulator bridging innate and adaptive immunity. Issue 1 (1st January 2019) - Zhou, Kai-Liang; Li, Xin; Zhang, Xiao-Lian; Pan, Qin
ABSTRACT: Mannose-capped lipoarabinomannan (ManLAM) is a high molecular mass amphipathic lipoglycan identified in pathogenic Mycobacterium tuberculosis ( M. tb ) and M. bovis Bacillus Calmette-Guérin (BCG). ManLAM, serves as both an immunogen and a modulator of the host immune system, and its critical role in mycobacterial survival during infection has been well-characterized. ManLAM can be recognized by various types of receptors on both innate and adaptive immune cells, including macrophages, dendritic cells (DCs), neutrophils, natural killer T (NKT) cells, T cells and B cells. MamLAM has been shown to affect phagocytosis, cytokine production, antigen presentation, T cell activation and polarization, as well as antibody production. Exploring the mechanisms underlying the roles of ManLAM during mycobacterial infection will aid in improving tuberculosis (TB) prevention, diagnosis and treatment interventions. In this review, we highlight the interaction between ManLAM and receptors, intracellular signalling pathways triggered by ManLAM and its roles in both innate and adaptive immune responses.